2011
DOI: 10.1007/s11845-011-0765-6
|View full text |Cite
|
Sign up to set email alerts
|

Reducing preoperative fasting in elective adult surgical patients: a case–control study

Abstract: Implementation of this protocol for reduced preoperative fasting achieved an appreciable reduction in fasting times and enhanced patient comfort. Patient safety was not compromised. Further modifications of our protocols are necessary to meet the international best practice. We recommend its implementation across all surgical groups in our institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 20 publications
1
44
0
6
Order By: Relevance
“…The adverse effect of fasting for longer duration on glucose metabolism has already been reported. 5,6,15,16 The results of this study showed that resistance to insulin was increased only in patients who underwent standard pre-operative fasting and similar findings were observed by Diana Borges DockNascimento et al (2012) in their study. 11 In our study Glutamine group showed benefits in improving insulin resistance when compared to other groups.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The adverse effect of fasting for longer duration on glucose metabolism has already been reported. 5,6,15,16 The results of this study showed that resistance to insulin was increased only in patients who underwent standard pre-operative fasting and similar findings were observed by Diana Borges DockNascimento et al (2012) in their study. 11 In our study Glutamine group showed benefits in improving insulin resistance when compared to other groups.…”
supporting
confidence: 88%
“…2 Standard fasting times are frequently longer than the expected 6e8 h, and may be as long as 10e16 h. 3 Fasting of prolonged duration is deleterious for the patient because the post-operative period is characterized by increased metabolic rate, hyper catabolism, gluconeogenesis and insulin resistance, 4 and is a key determinant of post-operative outcome and an independent predictor of the length of hospital stay after surgery. 5 Enhanced Recovery after Surgery (ERAS) protocol has recently gained attention as an evidence-based method for peri-operative care used in hospitals worldwide to improve patient prognosis and this protocol recommends carbohydrate loading via oral administration before surgery, which reduces thirst, hunger, anxiety, and nausea, while preventing muscle wasting and loss of nitrogen and protein. Furthermore, the ERAS protocol has been shown to prevent the aggravation of insulin resistance that occurs as a result of surgery.…”
mentioning
confidence: 99%
“…Taken together, these studies provide compelling evidence that loss of commensal microbiota at niches that affect stem cell function (i.e., crypts) may impact recovery. Clinical studies support the notion that the degree of starvation alone may adversely affect postoperative recovery (9, 17, 21, 24). …”
Section: Discussionmentioning
confidence: 77%
“…The implementation of the protocol reduced the fasting periods and contributed to other aspects that significantly improved the postoperative evolution, such as the reduction of the nasogastric tube use, early oral nutrition and early mobilization (12) . In another study that analyzed a control group that followed traditional fasting, being deprived of food and fluids and an intervention group that received fluids up to two hours before the surgery and solid foods up to six hours, it was verified that the intervention group showed less preoperative symptoms, such as hunger, headache and nausea, besides signs of feeling more comfortable (13) . Another prospective study observed that patients who fasted for a shorter period had less postoperative symptoms like nausea and vomiting (14) .…”
Section: The Projects Enhanced Recovery After Surgery (Eras) and The mentioning
confidence: 99%